Differential developmental refinement of the intrinsic electrophysiological properties of CA1 pyramidal neurons from the rat dorsal and ventral hippocampus. Issue 3 (6th September 2019) - Dougherty, Kelly A.
Abstract: The dorsal and ventral regions of the rat longitudinal hippocampal axis are functionally distinct. That is, each region is associated with different behavioral tasks and disease susceptibilities due to underlying anatomical, and physiological differences. These differences are especially pronounced in area CA1, where significant differences in morphology, synaptic physiology, intrinsic excitability, and gene expression have been reported between CA1 pyramidal neurons from the dorsal (DHC) and ventral hippocampus (VHC). However, despite a significant amount of recent attention, a cogent picture of the intrinsic electrophysiological profile of DHC and VHC neurons has remained elusive, due, in part, to experiments performed on rats at different developmental time points. Moreover, the resulting intrinsic electrophysiological profiles are sufficiently different as to warrant a thorough investigation of the spatial and temporal changes in the intrinsic excitability of CA1 pyramidal neurons across developmental time. Accordingly, in this study, I have characterized the intrinsic electrophysiological properties of CA1 pyramidal neurons from acute hippocampal slices prepared from the DHC and VHC throughout an approximately 3‐week developmental period (P14–P37). DHC and VHC neurons exhibited distinct intra‐region changes (DHC or VHC) and inter‐region differences (DHC versus VHC) in their intrinsic electrophysiological properties, which yielded two developmental timelines: (a) a common developmental timeline describing changes observed in both DHC and VHC neurons, and (b) a differential developmental timeline highlighting unique features observed in DHC neurons. Specifically, DHC neurons exhibited significant inter‐region differences in RMP, input resistance, threshold, and spike frequency adaptation relative to VHC neurons, as well as an intra‐region change in the rebound slope (a proxy for I h ). These observations both integrate and reconcile previous work performed with rats at different developmental stages and suggest a distinct developmental trajectory for DHC neurons that might shed light on the normal physiological functions and disease susceptibility of the DHC.